Effects of democracy, social inequality and economic growth on climate justice: An analysis with structural equation modelling - Furlan, Marcelo [UNESP]; Mariano, Enzo Barberio [UNESP] (Wiley, 2024)
The purpose of this paper was to assess the effects of social inequality, democracy, and economic growth on the climate justice performance of a nation. To achieve this goal, the research technique Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to a sample of 133 countries selected based on indicators available in international databases in 2019. The main results of the analysis were: (a) the effect of democracy on the performance of climate justice is positive; (b) the moderating effect of inequality on the relationship between democracy and climate justice is negative; and (c) economic growth has a U-shaped relationship with climate justice performance, which indicates the existence of a Kuznets curve for climate justice performance. Based on these results, the main theoretical implications of this study were the discoveries that: (a) the weakening of democratic institutions may be associated with increased social inequality, which reduces the implementation of climate policies aimed at guaranteeing justice; (b) forms of cooperation and financing of climate actions at the global level may be ineffective only if the quality of democracy in vulnerable countries is observed, which can be explained by the persistence of high social inequality; (c) allowing women access to income, education and health might be ways of reducing gender inequality and improving the level of adaptation of countries vulnerable to climate challenges.
Keywords: climate justice; democracy; FIMIX; Gaussian copula approach; inequality; structural equation modelling